THE MAIN FEATURES OF DEVELOPING LOGICAL THINKING OF STUDENTS IN CONDITIONS OF EDUCATION DIGIATALIZATION - Vlasii, Olesia; Dovgij, Oleg (Mountain School of Ukrainian Carpaty, 2019)
The article is devoted to research of the actual [рroblem of developing logical thinking of students in conditions of education digitalization. The aim of the research is analysis of the existing state of the problem of developing logical thinking of students and search of the ways of development of logical thinking using digital technologies. The main tasks of the present research are following: to analyze the role and place of logical thinking in a digital society; to analyze the available foreign and Ukrainian digital educational resources for the development of logical thinking of children of all ages; to separate the digital educational resources that could be used in the educational process in the study of mathematics and computer science; to analyze the possibilities of creating logical tasks using digital technologies. The main results of the research are follow: the place and role of logical thinking in the context of education digitalization is investigated; the place of logical thinking in the system of competence approach to studying in the New Ukrainian school is analyzed; the importance of the development of logical thinking for the formation of key competences of the person of the 21st century is established, in particular for mathematical and information-digital competencies; an overview of open e-learning resources for developing logical thinking of children and adults is presented; the digital educational resources that are appropriate to use in the educational process for the development of logical thinking are highlighted and examples of their using are given; there are given outlines prospects for further research in this area, which consist in a detailed analysis of the features of the process of developing digital educational resources and investigating ways of creating digital educational resources by modern creative educators for the development of logical and creative thinking of students.